A digital microfluidic droplet generator produces self-assembled supramolecular nanoparticles for targeted cell imaging - Liu, Kan (2010)
Controlling the size distribution of polymer-based nanoparticles is a challenging task due to their flexible core and surface structures. To accomplish such as task requires a very precise control at the molecular level. Here, we demonstrate a new approach whereby uniform-sized supramolecular nanoparticles (SNPs) can be reliably generated using a digital microfluidic droplet generator (DMDG) chip. A microfluidic environment enabled precise control over the processing parameters and, therefore, high batch-to-batch reproducibility and robust production of SNPs with a very narrow size distribution could be realized. Digitally adjusting the mixing ratios of the building blocks on the DMDG chip allowed us to rapidly scan a variety of synthesis conditions without consuming significant amounts of reagents. Nearly uniform SNPs with sizes ranging from 35 to 350 nm were obtained and characterized by transmission electron microscopy and dynamic light scattering. In addition, we could fine-tune the surface chemistry of the SNPs by incorporating an additional building block functionalized with specific ligands for targeting cells. The sizes and surface properties of these SNPs correlated strongly with their cell uptake efficiencies. This study showed a feasible microfluidic-assisted SNP production and provided a great means for preparing size-controlled SNP with desired surface ligand coverage.